A correlation between formation of free radicals and double bonds conversion during photopolymerization by EPR and NIR study and complex systems theory approach - Kavetskyy, T.S.; Matskiv , O.I.; Šauša , O.; Švajdlenková , H.; Soloviev , V.M.; Bielinskyi , A.O.; Tuzhykov, A.V.; Ostrauskaite , J.; Kiv , A.E. (Physics and Chemistry of Solid State, 2026)
The photopolymerization of acrylated epoxidized soybean oil (AESO) and vanillin dimethacrylate (VDM) with a photoinitiator (2,2-dimethoxy-2-phenylacetophenone) (DMPA) is studied by using electron paramagnetic resonance (EPR) and near-infrared (NIR) spectroscopy methods. A correlation between a concentration of free radicals deduced from EPR spectra and double bond conversion peak area deduced from NIR spectra as a function of UV-irradiation time for the investigated polymer composite is detected. The observed correlation is agreed well with the prediction of photopolymerization and photodegradation phenomena within a complex systems theory approach.